Structural, thermal and magnetic studies of MgxZn1−xFe2O4 nanoferrites: Study of exchange interactions on magnetic anisotropy. Issue 16 (December 2016) - Singh, S.B.; Srinivas, Ch.; Tirupanyam, B.V.; Prajapat, C.L.; Singh, M.R.; Meena, S.S.; Bhatt, Pramod; Yusuf, S.M.; Sastry, D.L.
Abstract: Polycrystalline nanoferrites with chemical formula Mgx Zn1−x Fe2 O4 ( x =0.5, 0.6, 0.7) have been synthesized by co-precipitation technique and then subsequently heated to 800 °C in order to investigate structural, thermal and magnetic properties. The samples are characterized by using XRD, FTIR, TGA-DSC, SQUID and Mössbauer spectroscopy techniques. The synergic effect of heat treatment with substitution of Mg 2+, results in random variation of lattice parameter ( a ) and crystallite size ( D ). FTIR studies revealed the formation of cubic spinel structure. The broadening at octahedral bands for compositions x =0.6 and 0.7 attributes to distribution of ferrite particles of different sizes in these samples. The characteristic feature of hysteresis loops reflects the nature of ferrite particles in the state of superparamagnetism. The saturation magnetization at room temperature has been reported for composition x =0.7 is 44.03 emu/g. The variation of coercivity is due to variation in magnetic anisotropy which is predominately affected by the exchange interactions arising from the nature of nanoparticles. The blocking temperatures are in the range of 10–30 K and their variation is in the line of change in magnetocrystalline anisotropy but not due to variation in crystallite sizes. The Zeeman splitting at tetrahedral (A) and octahedral (B) sites for composition x =0.6 is expected due to increase in size of core of the nanoparticles/or increasing of magnetocrystalline anisotropy. The range of isomer shift values and quadruple splitting values are evident for the presence of Fe 3+ ions and the absence of Fe 2+ ions in the present systems. The present ferrite nanoparticles in the superparamagnetic state are the potential candidates for biomedical applications like cancer treatment through hyperthermia. The results are interpreted in terms of cation redistribution presuming exchange coupling energy variation on magnetocrystalline anisotropy.